Host Control in Turn-Taking: A Conversation Analysis of Jimmy Fallon’s Interview with Jesse Eisenberg - Ghina Mayona Shanef; Zia Hisni Mubarak (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This article investigates how host control is interactionally achieved through turn-taking mechanisms in a late-night talk show interview. The data are drawn from an interview between Jimmy Fallon and Jesse Eisenberg on The Tonight Show Starring Jimmy Fallon. Using Sacks, Schegloff, Jefferson, (1974) theory of turn-taking as the sole analytical framework, this study employs qualitative conversation analysis to examine how the host manages speaking rights, regulates turn transitions, and maintains conversational structure. The findings indicate that host control is realized through strategic turn allocation, timely interruptions, cooperative overlaps, and the manipulation of Transition Relevance Places (TRPs). These practices allow the host to sustain conversational flow while preserving an informal, humorous atmosphere. The study demonstrates that host control operates as an interactional accomplishment rather than an explicit exercise of authority.